Analysis of Clothing Air Gap in a Protective Suit According to the Body Postures (Journal of Fiber Bioengineering and Informatics, 2014)
In dangerous working environments such as a Chemical, Biological and Radiological (CBR) exercise, aprotective suit plays an important role to increase work efficiency as well as prevent fatal damages. Airgaps entrapped in protective suit play an especially important role in heat transfer. The distributionand size of air gaps depends on body motions. The study developed 8 representative body motions(stretching, walking, crawling, crouching, twisting, climbing and reaching, moving weights and lateralbending) of CBR exercises of which 2 ∼ 4 static body postures per each motion were derived. 3D bodyscan was conducted on one male participant for the postures listed. Scanning was performed on bothnude and dressed bodies to measure the distribution and size of air gaps between human body andclothing. As a result, curves and volume of the air gaps varied with the different postures. The resultsserve as the basic data to improve protective performance of current protective suit.